Nahum, Habakkuk and Zephaniah an introduction and commentary - Baker, David Weston, 1950- (Leicester, UK IVP, 1988)
Includes bibliographcial references.
Keywords: Bible. O.T. Nahum -- commentaries; Bible. O.T. Habakkuk -- commentaries; Bible. O.T. Zephaniah -- commentaries